Low-cost plantain fiber composite as an alternative material for auto body fenders: A performance and manufacturing cost comparison - Jeremiah, Obiafudo Obiora; Madubueze, Ofochebe Sunday; Chimezie, Anyaora Sunday; Ekwueme, Godspower Onyekachukwu (Humanities Horizon, 2025)
High density polyethylene composite reinforced with natural plantain fiber was produced using injection moulding technique. The production process utilized the popular L18 Taguchi experimental design to investigate the effects of the major process variables such as barrel temperature, mold temperature, injection pressure, holding pressure, back pressure, clamping force and shaft speed in the final mechanical property of the composite material. The mechanical tests conducted on the new material reveal that fiber volume fraction of 0.1 combined with particle size of 75 μm and compactibilizer mass of 0.00024 kg gives a high-quality composite material suitable for auto body fender application, at reduced manufacturing cost of ₦1454/kg of the composite. The composite material produced at optimized process condition was found to have tensile strength of 87.44 MPa, yield strength of 76.6 MPa, flexural strength of 77.03 J, Rockwell hardness strength of 756.99, Impact strength of 16.21 J and density of 993 kg/m3. The result shows that the auto body fender produced based on the compactibilized plantain fiber reinforced high-density polyethylene composite has an advantage of low density and reduced production cost compared to conventional/alternative materials.